Match workload in female football players vary across menstrual cycle phases - Antero, J.; Chassard, T.; Blanquet, L.; Delarochelambert, Q.; Toussaint, J. F. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Sex hormones variations seem to impact work load among female football players. Quantitative measures of load parameters across either the menstrual cycle (MC) or combined oral contraception (OC) phases are scarce. We aimed to quantify the players match load across their MC or OC phases of a French National club trough an entire season.